MOTIVASI ALUMNI D3 MELANJUTKAN STUDI KE JENJANG S1 PENDIDIKAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Juwita, Vera; Zahri, Wildati; Rahmiati, Rahmiati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The aim of D3 study program based on the academic guiding book of UNPis to be the professional and can do entrepreneur, and the aim of Family WelfareDepartment (S1) is to be the teachers. But in fact, the graduate of D3 have lessdesire to be an entrepreneur, and most of them continue their study to S1 familywelfare department and wants to me the civil official.The kind of this research is quantitative using descriptive method. Thepopulation is all D3 fashion department graduates that continue their study to S1education in Family Welfare Department UNP who registered in January – June2013, which are 33 persons. All population are the samples. The data processedby using percentage and data categorizing.The result shows that 55% respondents have high motivation to continuetheir study to S1 Family Welfare department due to their future dream, 52%respondents have high motivation to continue their study to S1 Family Welfaredepartment due to their family support, 36% respondents have medium motivationto continue their study to S1 Family Welfare department due to the times.Kata kunci: Motivasi, Melanjutkan Studi